Two-dimensional and three-dimensional cell culture models in vitro: pros and cons - E. S. Galimova; M. М. Galagudza (Бюллетень сибирской медицины, 2018)
Discovery and development of new chemical compounds with putative anti-cancer properties requires reliable predictive preclinical models for in vitro screening of efficacy. Such models mainly include cultures of human cancer cells: two-dimensional (2D) and three-dimensional (3D) cell culture systems. In this review, we discuss the molecular aspects of cells cultured in 2D and 3D, and their relevance to cancer study, focusing on key examples from the recent literature. Advantages, disadvantages and perspectives of described models are also analyzed.